Noninvasive Methods, including Transient Elastography, for the Detection of Liver Disease in Adults with Cystic Fibrosis - Matthew D Sadler; Pam Crotty; Linda Fatovich; Stephanie Wilson; Harvey R Rabin; Robert P Myers (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Liver disease is the third leading cause of mortality in patients with cystic fibrosis (CF). However, detection of CF-associated liver disease (CFLD) is challenging.